Phylogeny and genetic diversity of two solitary African mole-rat genera Heliophobius and Georychus - Uhrová, Michaela (Jihočeská univerzita, 2020)
Two solitary genera of African mole-rats, Heliophobius and Georychus, had been for a long time considered as monotypic, yet some of the recent studies proposed species complexes. This thesis evaluates intrageneric relationships of both genera by using extended dataset of six nuclear markers and a large number of loci acquired during ddRADseq. Both datasets confirmed highly genetically structured populations within both genera. Nevertheless, while multilocus coalescent based on nuclear markers defined nine gene pools within Heliophobius and five within Georychus, processing of ddRADseq data revealed both, significantly finer (fineRADstructure) or broader (Infomap) structure. Based on the genetic evidence, we are inclined towards using two species within genus Heliophobius, comprised of northern and southern lineages separated by Eastern Arc Mountains, and one species for all evolutionary lineages of Georychus. The final taxonomic revision should await further morphological, ecological, or behavioural studies.
Phylogeny and genetic diversity of two solitary African mole-rat genera Heliophobius and Georychus
Keywords: Heliophobius; Georychus; phylogeny; ddRADseq